思考歷史能動力：原住民立足點與批判的展演政治 - Chang, Chun-Mei (Taiwan She Hui Xue Kan, 2017)
The starting point of this essay is the possibility of a critical historical agency in Taiwan. The first section introduces the author's view of the organic connection between the theoretical and the empirical. The second section describes the pitfalls of the popular dichotomy of Chinese-versus- Taiwanese identities, especially its omission of the indigenous peoples' historical situation and consciousness. The third section draws on Judith Butler's performative theory of political discourse to clarify the situational ambiguity and possibilities of historical agency. The fourth section articulates the theoretical and political significance of the indigenous conception of history for Taiwan's multiple positions of enunciation, and its connections to the indigenous standpoints in Australia and other countries. In my conclusion, I propose a performative politics involving the concepts of standpoint and coalition.